Antibody-Dependent Cellular Cytotoxicity Activity of Effector Cells from HIV-Infected Elite and Viral Controllers - Isitman, Gamze; Lisovsky, Irene; Tremblay-McLean, Alexandra; Kovacs, Colin; Harris, Marianne; Routy, Jean-Pierre; Bruneau, Julie; Wainberg, Mark A; Tremblay, Cécile; Bernard, Nicole F (AIDS research and human retroviruses, 2016)
Carriage of alleles encoding certain inhibitory natural killer (NK) cell receptor/HLA ligand KIR3DL1/HLA-B combinations is associated with protection from HIV infection and slow time to AIDS, implicating NK cells in HIV control. NK cells also mediate antibody-dependent cellular cytotoxicity (ADCC). ADCC has been identified as a correlate of protection in secondary analyses of the modestly protective RV144 Thai HIV vaccine trial. In ADCC, HIV envelope (Env)-specific antibodies (Abs) bridge HIV-infected or gp120-coated target cells and NK cells expressing CD16 receptors for Ab Fc domains. CD16 engagement activates NK cells to secrete cytokines/chemokines, degranulate, deliver granzyme B (GrB) to target cells, and cytolysis. A subset of HIV+ subjects, known as slow progressors (SPs), maintains low-level viremia without treatment. HIV+ SPs versus progressors have higher titers and/or a greater breadth of ADCC-competent Abs. Investigations of the functional capacity of NK effector cells following CD16 engagement in HIV+ subjects are lacking. We used the ADCC-GranToxiLux (ADCC-GTL) assay to assess the frequency of GrB+ (%GrB+) cells generated by effector cells from 37 HIV+ SPs and 15 progressors to gp120-coated CEM.NKr.CCR5 target cells in the presence of anti-Env Abs. Subject groups were stratified according to whether or not they carried educating KIR3DL1/HLA-B combinations able to confer NK cells with functional potential. No differences were observed in %GrB+ target cells generated by effector cells from carriers of educating versus noneducating KIR3DL1/HLA-B pairs. The absence of an effect of NK cell education on this readout may be due to loss of the ability of educated NK cells from SPs to respond to Ab-dependent stimulation and/or the lower frequency of KIR3DL1 than KIR3DL1 NK cells that coexpress CD16. That KIR/HLA genotypes have minimal impact on interindividual differences in ADCC potency has relevance for therapeutic interventions that target ADCC for HIV control.